2014
DOI: 10.1089/pho.2014.3782
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Four Surface Conditioning Methods on the Shear Bond Strength of Metal Bracket to Porcelain Surface

Abstract: Objective: This study evaluated the effect of superpulse CO 2 laser irradiation and deglazing of porcelain surfaces on the shear bond strength (SBS) of metal orthodontic brackets, and compared it with two conventional etching techniques. Methods: Forty-eight Feldspathic porcelain fused to metal specimens embedded in cylindrical acrylic resin tubes were fabricated, and all the specimens were divided into four groups. In Group 1, the specimens were roughened with a diamond bur and etched with hydrofluoric acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 32 publications
(67 reference statements)
0
19
1
Order By: Relevance
“…A recent study 12 found that fractional CO2 laser has better performance when used on deglazed than glazed feldspathic porcelain for bonding metal orthodontic brackets. However, Zarif Najafi et al 26 concluded that deglazing is not a mandatory step before application of CO2 laser for surface preparation of feldspathic porcelain. In the present study, the use of HF acid provided bond strength value that was significantly greater than that of the air-abraded and laser-treated specimens.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study 12 found that fractional CO2 laser has better performance when used on deglazed than glazed feldspathic porcelain for bonding metal orthodontic brackets. However, Zarif Najafi et al 26 concluded that deglazing is not a mandatory step before application of CO2 laser for surface preparation of feldspathic porcelain. In the present study, the use of HF acid provided bond strength value that was significantly greater than that of the air-abraded and laser-treated specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrofluoric acid is cited as being a ceramic surface conditioner because of its capacity to promote the morphological changes necessary for bonding [1][2][3][4][5] . The growing need for esthetic rehabilitation has raised the demand for orthodontic treatment and increasingly improved alignment of teeth.…”
Section: Introductionmentioning
confidence: 99%
“…The literature has suggested surface treatment options for the purpose of promoting enamel surface roughness before bracket bonding 1,6 . Roughness may be achieved by mechanical means using diamond tips or airborne particle abrasion with aluminum oxide particles 1,6 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations